Clinical research coordinators' role in knowledge translation activities in rehabilitation: a mixed methods study - P. Kengne Talla; C. Robillard; S. Ahmed; A. Guindon; C. Houtekier; A. Thomas (BMC, 2023)
Abstract Background Clinical research coordinators (CRCs) facilitate the interaction between researchers and knowledge users in rehabilitation centres to promote and sustain evidence-informed practices. Despite their presence in rehabilitation settings in Quebec for over 20 years, little is known about their profiles and knowledge translation (KT) activities nor how they can best enact their role. This study explored CRCs' roles and perspectives on the barriers, enablers, and strategies for improving KT activities in rehabilitation settings. Methods We conducted a multi-centre, participatory sequential mixed methods study. In the descriptive quantitative phase, we collected data via an online survey to determine CRCs' role in research and KT. In the subsequent qualitative phase, we conducted an in-person focus group to elicit CRCs' perspectives regarding factors influencing their work in KT, and potential solutions for overcoming these challenges. We used a descriptive and an inductive content analysis approach for the data analysis. The data synthesis was inspired by the Promoting Action on Research Implementation in Health Services framework. Results All nine CRCs from five partner health regions of a large rehabilitation research centre agreed to participate in the study. The data suggest that CRCs are like knowledge brokers and boundary spanners. As information managers, linkage agents and facilitators, CRCs play a pivot role in diffusion, dissemination, synthesis and tailoring of knowledge to improve evidence informed practices and quality of care in rehabilitation. The factors influencing CRCs' KT activities are mostly linked to the context such as the receptivity of the organization as well as the lack of time and resources, and limited understanding of their roles by stakeholders. Two main suggestions made to enhance CRCs' contribution to KT activities include the harmonisation of expectations between the large research centre and their partner health regions, and better promotion of their role to clinical and research teams. Conclusions This study provides valuable insights into the scope of CRCs' role. The results shed light on the challenges that they face and potential solutions to overcome them. The knowledge generated in this study can be used to implement this role with similar duties in rehabilitation settings or other health care domains.